O professor da educação infantil e a contação de histórias - Silva, Valéria (2018)
This research consists of a field work, whose participants are teachers in the field of early chidhood education that tell stories. The objective of the study is to get acquainted with the conceptions of storytelling analyzing how literature is taken into the schools, as the choices are made and how the teachers use them, identify if there are evidences of any relation between the storytelling and the student’s reality. The text structure is configured in five chapters. The first: “Histories that defined the itinerary of my life”, it highlights how the stories present in my formation, from the family context, the academic periods, academic and professionals, consubstantiated in the research problems. In the second chapter, "The paths covered in the construction of research" I present the interpretive methodology based on the hermeneutical approach that made it possible to understand the meaning of the participants' actions and to interpret them as the stories present in my formation, from the family context, periods students, academics and professionals, consubstantiated the research problem. The instruments selected for the field work were: reflexive interview, documentary analysis and focus group. The third chapter, "Storytelling: Revisiting Concepts and Practices" discusses the context that permeates stories, pathways, innovation capacity in the technological age, and relevance in the educational setting. The fourth chapter: "Storytelling in the context of early childhood education: conceptions and practices" - presents the data analysis, which showed the conceptions and practices of teachers in regard to storytelling; reveals and simultaneously generates discoveries of the choices and criteria of literature; clarifies what is taken to the schools from the conceptions of what the teachers believe to be literature, shows that they use as criterion of approaches of the histories the orientations contained in the axes of work proposed by the SME. The teachers also interface with the reality of the students considering their needs and emergency demands that arise in the daily school. To finish the research I close with the chapter: "The plots of history". This part of the text points to the final considerations; I discover through the research that the teachers believe to approach the literature in an "adequate" way, but not always it is effective at the moment of practice. Research allows us to reflect by the action-reflection-action movement on the teaching profession.